Testing through the Mann-Whitney Method and the Wilcoxon Signed Level on Learning Cube and Perfect Cube Roots - Endro Tri Susdarwono (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2021)
The purpose of this study is to discuss the testing using the Mann-Whitney method and the Wilcoxon signaled level for learning perfect cube and cube root. This research is a quantitative study, while the method used is experimental. The quantitative approach used includes the Mann-Whitney test and Wilcoxon's signed rank test. The conclusions of this study are that: 1) for the Mann-Whitney test on the pretest value of the control group and the experimental group it is concluded that before the treatment of two groups, namely control and experiment, had the same ability in mastering the material to the third power and the cube root; 2) For the Mann-Whitney test on the post-test scores of the control group and the experimental group, it is concluded that after the treatment of two groups, namely the control and the experimental group, they have different abilities in mastery of the material in the third power and the cube root; whereas 3) for the Wilcoxon-signed level test on the pretest and posttest scores of the experimental group, it was concluded that there was a difference between the conditions before and after being given treatments on the mastery of the material to the third power and the perfect cube root.